The The Effect of Location, Personal Selling and Price Perception on Consumer Purchasing Decision in Property Company, North Bekasi District - Andrian; Neng Siti Komariah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of location, personal selling and price perception of consumer purchasing decisions at PT. Symbol Nusantara Land housing. This type of research is quantitative. The population in this study amounted to 50 people. Sampling technique using saturated sampling technique. The sample in this study amounted to 50 respondents. Data collection techniques by distributing questionnaires through Google Form. Hypothesis testing in this study using Multiple Linear Regression analysis. The research subjects are consumers who have ordered and who have occupied a housing unit at PT. Symbol Nusantara Land. The results of this study indicate that the variables of Location, Personal Selling and Price Perception partially and simultaneously have a significant and positive effect on the Purchasing Decision variable.